The fellowship of the ring : being the first part of The Lord of the Rings - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973 (Tolkien, J. R. R. (John Ronald Reuel), 1892-1973. Lord of the rings, 2012)
After discovering the true nature of the one ring, Bilbo Baggins entrusts it to the care of his young cousin, Frodo, who is charged with bringing about its destruction and thus foiling the plans of the Dark Lord.